Additive interactions of some reduced-risk biocides and two entomopathogenic nematodes suggest implications for integrated control of Spodoptera litura (Lepidoptera: Noctuidae) - Rashad Rasool Khan (Nature Portfolio, 2021)
Abstract Higher volumes of conventional and novel chemical insecticides are applied by farmers to control resistant strains of armyworm (Spodoperta litura) in Pakistan without knowing their risks to the environment and to public health. Ten reduced-risk insecticides were tested for their compatibility with two entomopathogenic nematodes (EPNs); Heterorhabditis indica and Steinernema carpocapsae against S. litura. The insecticide emamectin benzoate was highly toxic (LC50 = 2.97 mg/l) against 3rd instar S. litura larvae when applied alone whereas, novaluron and methoxyfenozide were the least toxic (LC50 = 29.56 mg/l and 21.06 mg/l), respectively. All the insecticides proved harmless against the two EPNs even 96 h after treatment. Indoxacarb, flubendiamide and spinetoram produced the greatest mortalities (72–76%) of S. litura larvae after 72 h when applied in mixtures with H. indica. Lowest mortalities (44.00 ± 3.74% and 48.00 ± 2.89) were observed for mixtures of H. indica with methoxyfenozide and chlorfenapyr, respectively. The positive control treatments with both EPNs (S. carpocapsae and H. indica) produced > 50% mortality 96 h after treatment. For insecticide mixtures with S. carpocapsae, only indoxacarb produced 90% mortality of larvae, whereas, indoxacarb, flubendiamide, emamectin benzoate, and spinetoram produced 90–92% mortality of larvae when applied in mixtures with H. indica. Additive interactions (Chi-square < 3.84) of EPN mixtures with reduced volumes of reduced-risk insecticides suggest opportunities to develop more environmentally favorable pest management programs for S. litura.